2014
DOI: 10.1590/0034-737x201461040005
|View full text |Cite
|
Sign up to set email alerts
|

Custo de produção e lucratividade da cultura do amendoim no município de Jaboticabal, São Paulo

Abstract: O Estado de São Paulo é o maior produtor de amendoim do Brasil e a produção concentra-se na região de Ribeirão Preto, onde o cultivo é realizado em áreas arrendadas, em esquemas de sucessão e rotação, principalmente, para reforma de canaviais. Nesse caso, a rotação com amendoim durante a entressafra é escolha viável, pois além de poder ser rentável, as terras que ficariam ociosas mantêm a sua produtividade. Por esta razão, o objetivo deste trabalho foi estimar e analisar o custo de produção e a rentabilidade d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 2 publications
0
19
0
9
Order By: Relevance
“…The methodology of the calculation of cost production used was that of the IEA (Instituto de Economia Agrícola), described in Barbosa et al (2014). The factors considered in the production system were: effective operational cost (EOC), which are the expenses incurred with labor, machinery/equipment operations and materials consumed throughout the production process; and total operational cost (TOC), which is the actual operating cost plus expenses with direct social charges, rural social security contribution, financial charges, technical assistance and machine depreciation.…”
Section: Subject Descriptionmentioning
confidence: 99%
“…The methodology of the calculation of cost production used was that of the IEA (Instituto de Economia Agrícola), described in Barbosa et al (2014). The factors considered in the production system were: effective operational cost (EOC), which are the expenses incurred with labor, machinery/equipment operations and materials consumed throughout the production process; and total operational cost (TOC), which is the actual operating cost plus expenses with direct social charges, rural social security contribution, financial charges, technical assistance and machine depreciation.…”
Section: Subject Descriptionmentioning
confidence: 99%
“…It is observed that the value of the lease is high, as well as the amount spent on seeds and inputs, since the peanut crop has low physiological potential, being susceptible to attack by diseases and pests. The representativeness of these costs was also found by Barbosa et al (2014).…”
Section: Resultsmentioning
confidence: 79%
“…The research method is a case study for a property with peanut production in the Jaboticabal-SP region, which was chosen in an intentional and non-probabilistic way, due to its representativeness in peanut cultivation in the State of São Paulo, besides having the largest peanut processing unit in the country, which receives, stores, markets, and exports the grain -Cooperativa Agroindustrial de Jaboticabal (COPLANA) (Compagnon et al, 2013;Barbosa et al, 2014). The case study was used to allow the results to be understood by other agents, with a greater interaction between the researcher and the studied context.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations